2016
DOI: 10.1038/srep27856
|View full text |Cite
|
Sign up to set email alerts
|

Association of RSV-A ON1 genotype with Increased Pediatric Acute Lower Respiratory Tract Infection in Vietnam

Abstract: Since the initial discovery of RSV-A ON1 in Canada in 2010, ON1 has been reported worldwide, yet information regarding its clinical impact and severity has been controversial. To investigate the clinical relevance of RSV-A ON1,acute respiratory infection (ARI) cases enrolled to our population-based prospective pediatric ARI surveillance at Khanh Hoa General Hospital, Central Vietnam from January 2010 through December 2012 were studied. Clinical-epidemiological information and nasopharyngeal samples were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
47
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 48 publications
8
47
3
Order By: Relevance
“…In our hospitalized patients, no association was found between the circulating genotypes (GA2, ON, BA) with the severity of the lower respiratory tract disease. In contrast to recent reports [24,25,26], the recently described ON genotype did not show a higher severity score. As with the influenza virus, continuous surveillance may be needed to detect new emergent genotypes and to assess their immediate effect in susceptible populations.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In our hospitalized patients, no association was found between the circulating genotypes (GA2, ON, BA) with the severity of the lower respiratory tract disease. In contrast to recent reports [24,25,26], the recently described ON genotype did not show a higher severity score. As with the influenza virus, continuous surveillance may be needed to detect new emergent genotypes and to assess their immediate effect in susceptible populations.…”
Section: Discussioncontrasting
confidence: 99%
“…Many studies have reported the molecular epidemiology and genetic variability of RSV worldwide [10,11,12,13,14,15,16,17,18,19,20], revealing the emergence and spread of new genotypes with duplication of ~60 to 70 nucleotides in this G hypervariable region for RSV-A (RSV Ontario) and RSV-B (RSV Buenos Aires) [15,19,21,22]. Although none of the variants or genotypes has been consistently associated with greater virulence or pathogenicity [13,18,22,23], some recent reports describing clinical aspects of contemporary genotypes (NA1 and ON1) have shown higher frequencies of LRTI and hospitalizations rates [24,25,26]. …”
Section: Introductionmentioning
confidence: 99%
“…Based on the pattern of disease epidemics, we surmise that the NA1 genotype (ancestor of ON1) was replaced with the ON1 genotype during 2011 to 2012. Such substitutions were observed in studies conducted in other countries [23,25].…”
Section: Discussionsupporting
confidence: 65%
“…E. Park and others RSV-positive infections has been investigated continuously through various studies [16,23,25,28,36]. We performed two analyses with respect to the clinical relevance of RSV-positive infections.…”
Section: Clinical Symptomsmentioning
confidence: 99%
“…We concluded that the A/H1N1pdm09 outbreak occurred around mid‐2009 in our study site and assumed that a large population in the community might have been infected with this new A/H1N1pdm09 strain. This may have led to the development of non‐specific antiviral immunity in the target community, which may have disrupted the circulation trend of other respiratory viruses, including influenza B. Interestingly, we also observed unusual split of RSV seasonal peak in 2010 as we previously described . Further studies would be necessary to understand the effect of A/H1N1pdm09 on respiratory virus circulation trend.…”
Section: Discussionmentioning
confidence: 54%